2014
DOI: 10.1080/14616688.2014.915877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dimensions of place attachment on residents’ word-of-mouth behavior

Abstract: The purpose of this study is to examine and compare the effect of residents’ different dimensions of place attachment on their word-of-mouth (WOM) behavior in two cities: Sydney, Australia and Shanghai, China. A six-dimensional construct of place attachment is proposed based upon a detailed literature review: four attitudinal dimensions (place identity, place dependence, affective attachment, social bonding) and two interactional dimensions (place memory, place expectation) are proposed to reflect different as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 68 publications
7
90
1
2
Order By: Relevance
“…The latter showed that individuals form a match between their self-image and destination image (or image of a typical visitor of a destination), which influences their behaviour (intention to visit, intention to recommend, loyalty etc.). Placing a focus on destination visitors, the literature does not inform on the self-congruity effect among local residents, who also play a very important role in shaping destination image through place promotion (Chen, Dwyer and Firth, 2014b). In this sense, residents are considered to be tourists, who regularly use destination resources and also portray tourists' behaviour in their place of residence.…”
Section: Place Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter showed that individuals form a match between their self-image and destination image (or image of a typical visitor of a destination), which influences their behaviour (intention to visit, intention to recommend, loyalty etc.). Placing a focus on destination visitors, the literature does not inform on the self-congruity effect among local residents, who also play a very important role in shaping destination image through place promotion (Chen, Dwyer and Firth, 2014b). In this sense, residents are considered to be tourists, who regularly use destination resources and also portray tourists' behaviour in their place of residence.…”
Section: Place Attachmentmentioning
confidence: 99%
“…Previous research has found effects of these dimensions on specific behaviours related to the place such as retention and word-of-mouth intention (Chen, Dwyer and Firth 2014b;Chen, Dwyer and Firth 2015).…”
Section: Place Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our perceptions of places are built upon past experiences and evolve through new interactions, which are sometimes shared with others (e.g., Tuan, 1977;Gustafson, 2001;Massey, 2005;Chen et al, 2014). Imagined through a geological lens and coupled with a cultural lens, each landscape carries with it a heritage of past occupation and environmental change, and it is through the interplay between each individual and each landscape that a new sense of place is formed.…”
Section: Sense Of Place In the Fieldmentioning
confidence: 99%
“…Place attachment is composed of largely, but not exclusively, of the degree of dependence on and identity with a locality (e.g., Williams and Vaske, 2003;Kyle et al, 2005;Chen et al, 2014).…”
Section: Sense Of Place In the Fieldmentioning
confidence: 99%